KARAKTERISASI TERMOKOPEL TIPE K PADA FASILITAS SIMULASI SISTEM FASSIP-02 - Sumantri Hatmoko Hatmoko; Kussigit Santosa Santosa; Giarno Giarno Giarno; Dedy Haryanto Haryanto; Mulya Juarsa Juarsa; M Hadi Kusuma; Anhar Riza Antariksawan; Surip Widodo Widodo (Jurnal Ilmiah Teknik Mesin POROS, 2021)
In the activities of the Pratama Insinas, Ministry of Higher Education technology research in 2018, PTKRN BATAN built a testing facility that simulates a passive cooling system on the reactor core when there is a loss of outside power. The test facility is the Passive-02 System Simulation Facility (FASSIP02).In FASSIP-02 there are several parameters that need to be measured, one of which is temperature. In the measurement of temperature using a K type Thermocouple Connected to the National Instrument 9178 and 9213 modules that use computer programming with LabVIEW software. Temperature measurements need to be characterized.Characterization of type K thermocouples was carried out using thermobaths, 30 type K thermocouples, standard thermocouples,National Instrument modules 9178 and 9213 with computer programming displays using LabVIEW software. The method used for characterization oftype K thermocouples is a fixed temperature comparison method where the results of the temperature control of thermobath is 30-90 ͦC compared with the results of measurements from the type Kthermocouple and standard thermocouple. From the difference of the copper-wrapped junction tip thermocouple without the copper-wrapped and standard thermocouple produces a small error value, so the use of copper as a thermocouple junction end wrapper can be used as a temperature measurement FASSIP-02.